Relationship between volume and outcome for gastroschisis: a systematic review - Morche, Johannes; Mathes, Tim; Jacobs, Anja; Wessel, Lucas; Neugebauer, Edmund A. M.; Pieper, Dawid (Journal of pediatric surgery, 2022)
Background - Newborns with gastroschisis need surgery to reduce intestines into the abdominal cavity and to close the abdominal wall. Due to an existing volume-outcome relationship for other high-risk, low-volume procedures, we aimed at examining the relationship between hospital or surgeon volume and outcomes for gastroschisis. - Methods - We conducted a systematic literature search in Medline, Embase, CENTRAL, CINAHL and Biosis Previews in June 2021 and searched for additional literature. We included (cluster-) randomized controlled trials (RCTs) and prospective or retrospective cohort studies analyzing the relationship between hospital or surgeon volume and mortality, morbidity or quality of life. We assessed risk of bias of included studies using ROBINS-I and performed a systematic synthesis without meta-analysis and used GRADE for assessing the certainty of the evidence. - Results - We included 12 cohort studies on hospital volume. Higher hospital volume may reduce in-hospital mortality of neonates with gastroschisis, while the evidence is very uncertain for other outcomes. Findings are based on a low certainty of the evidence for in-hospital mortality and a very low certainty of the evidence for all other analyzed outcomes, mainly due to risk of bias and imprecision. We did not identify any study on surgeon volume. - Conclusion - The evidence suggests that higher hospital volume reduces in-hospital mortality of newborns with gastroschisis. However, the magnitude of this effect seems to be heterogeneous and results should be interpreted with caution. There is no evidence on the relationship between surgeon volume and outcomes.
Online verfügbar: 28. März 2022, Artikelversion: 15. November 2022
Gesehen am 02.09.2024